SHORT-TERM REPRODUCIBILITY OF AMBULATORY BLOOD PRESSURE MONITORING: A SYSTEMATIC REVIEW. (June 2018) - Lee, K.P.; Yip, B.; Wong, S.; Tsoi, K.; Kwong, J.; Chu, C.
Abstract : Objective: Ambulatory blood pressure monitoring (ABPM) is the recommended blood pressure (BP) measurement method to diagnose hypertension. Besides the absolute BP values, BP variability and nocturnal dipping on ABPM were found to predict cardiovascular outcomes. However, a comprehensive review of reproducibility of these ABPM parameters is lacking. Our objective is to systematically review the short-term reproducibility of ABPM. Design and method: A comprehensive search was performed on MEDLINE (PubMed) from database inception to December 2017. Included studies were (i) published in English and (ii) reported measures of short-term reproducibility of ABPM BP values/BP variability/dipping status in human adult subjects, for which at least 2 sessions of ABPM with a between-session time interval of less than or equal to 1 month were performed. Studies involving participants who were pregnant or were receiving haemodialysis were excluded. Results: Initial literature search identified 1043 titles and abstracts; of these, 86 full texts articles were retrieved for further assessment and eventually a total of 21 studies were included. Due to heterogeneity of the included studies, data pooling in the form of a meta-analysis was not possible. A qualitative synthesis was performed. The majority of studies used the Spacelabs ABP monitors and measured 24-hour, daytime and night-time systolic and diastolic BP in two sessions, with between-session time intervals ranging from 4 days to 1 month. Types of participants varied across studies and included normotensives, hypertensives as well as mixed cohorts. Most studies were conducted in western population. Sample size was generally small, ranging from 10 to 330. The included studies employed a wide array of methods to quantify reproducibility and the majority reported moderate to good short-term reproducibility of ABPM. Reproducibility of BP variability and dipping status was rarely studied. Conclusions: More studies about reproducibility of ABPM in various ethnic groups and in BP variability and dipping status are needed.